Na+/H+ exchanger NHE1 and NHE2 have opposite effects on migration velocity in rat gastric surface cells. Issue 7 (21st February 2017) - Paehler vor der Nolte, Anja; Chodisetti, Giriprakash; Yuan, Zhenglin; Busch, Florian; Riederer, Brigitte; Luo, Min; Yu, Yan; Menon, Manoj B.; Schneider, Andreas; Stripecke, Renata; Nikolovska, Katerina; Yeruva, Sunil; et al.
Abstract : Following superficial injury, neighbouring gastric epithelial cells close the wound by rapid cell migration, a process called epithelial restitution. Na + /H + exchange (NHE) inhibitors interfere with restitution, but the role of the different NHE isoforms expressed in gastric pit cells has remained elusive. The role of the basolaterally expressed NHE1 (Slc9a1) and the presumably apically expressed NHE2 (Slc9a2) in epithelial restitution was investigated in the nontransformed rat gastric surface cell line RGM1. Migration velocity was assessed by loading the cells with the fluorescent dye DiR and following closure of an experimental wound over time. Since RGM1 cells expressed very low NHE2 mRNA and have low transport activity, NHE2 was introduced by lentiviral gene transfer. In medium with pH 7.4, RGM1 cells displayed slow wound healing even in the absence of growth factors and independently of NHE activity. Growth factors accelerated wound healing in a partly NHE1‐dependent fashion. Preincubation with acidic pH 7.1 stimulated restitution in a NHE1‐dependent fashion. When pH 7.1 was maintained during the restitution period, migratory speed was reduced to ∼10% of the speed at pH 7, 4, and the residual restitution was further inhibited by NHE1 inhibition. Lentiviral NHE2 expression increased the steady‐state pHi and reduced the restitution velocity after low pH preincubation, which was reversible by pharmacological NHE2 inhibition. The results demonstrate that in RGM1 cells, migratory velocity is increased by NHE1 activation, while NHE2 activity inhibit this process. A differential activation of NHE1 and NHE2 may therefore, play a role in the initiation and completion of the epithelial restitution process. Abstract : Genetic deletion of the Na + /H + exchanger NHE2 leads to compromised wound healing in the gastrointestinal tract of mice. We studied the roles of NHE1 and NHE2 in gastrointestinal wound healing in vitro, and while NHE1 activity supported wound healing velocity, NHE2/GFP‐overexpression dramatically reduced wound healing velocity compared to GFP expression alone. This effect was abolished by a NHE2‐ but not a NHE1 inhibitory concentration of HOE642. Thus, NHE1 and NHE2 may be important for the initiation and the resolution of gastrointestinal wound healing.